Quantum negotiation : are you getting what you need? - Mardyks, Stephan, 1962-; Walch, Karen S.; Schmitz, Joerg (Hoboken : Wiley, 2017)
'The Quantum Negotiation preparation model explores who we are as negotiators in the context of our social conditioning. Our model explores all of our human dimensions in the cognitive, psychological, social, physical and spiritual fields. Quantum Negotiators have a strong sense of self, identity, and are anchored to their own values. However, Quantum Negotiators also have the curiosity, the resilience and the intelligence to understand another's point of view and interests'--
'The Quantum Negotiation preparation model explores who we are as negotiators in the context of our social conditioning. Our model explores all of our human dimensions in the cognitive, psychological, social, physical and spiritual fields. Quantum Negotiators have a strong sense of self, identity, and are anchored to their own values. However, Quantum Negotiators also have the curiosity, the resilience and the intelligence to understand another's point of view and interests'--
Includes bibliographical references and index.
Keywords: Negotiation in business; Leadership